DUNIA MODE DAN BIDANG USAHA PEMBUATAN BUSANA - Hotmaria Tampubolon (JURNAL KELUARGA SEHAT SEJAHTERA, 2017)
From time to time, clothing stores sell clothing with unique cutting styles. This piece of clothing style captured the hearts of buyers, so clothing that some time before was very popular, had to be abandoned, that's the appearance of a fashion phenomenon. By "fashion" is meant a way of dressing with a style cut or style that is more accepted by a group of people at a certain time. Fashion  that comes from the west, quickly imitated by men and women. Sometimes the mode initially gets criticized, because it feels unsuitable or clumsy. Gradually many people choose and follow the latest fashion for fear of getting the title "missed mode". Growing rapidly between nations, the more people recognize the various cultures affecting each other. This communication also influences the development of fashion. To follow the flow of fashion well, we need to know the basic style of a fashion that must reappear in the next mode with a difference in the short length of the skirt. Thus fashion that has a basic style will last longer, which means that fashion is not quickly behind fashion, so it also saves finance.